Introduction - OLIVER MTAPURI (African Journal of Governance and Development, 2017)
Given its abundance of minerals, human resources, good climatic conditions as well as its vast flora and fauna - we imagine an Africa brimming with vibrant economies girded by good governance; an Africa free from hunger and poverty and one that is in tune with the United Nations Sustainable Development Goals. In many parts of sub-Saharan Africa however, despite the adoption of the Millennium Development Goals in 2000, the vision of vibrant economies girded by good governance remains out of reach it would seem.